Rancang Bangun Aplikasi Penentuan Lokasi Layanan Umum Menggunakan Augmented Reality Berbasis Android - Atmaji, Lestanto; Sutanto, Teguh; Sukmaaji, Anjik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: Public service is a place to meet specific needs, where common services include restaurants, hotels, public refueling stations (gas stations), and automatic teller machine (ATM). At this time the search location of public services supported by the device commonly called a location search navigation system or guiding direction. Knowledge navigation system directions or compass and map, and how to use it must be owned and understood. Problems encountered were not all users can read a map, both in physical form and application service providers map. They have difficulty in the process of introducing a new area they visit with the map provided, therefore the knowledge of the directions or compass and map, and how to use it must be owned and understood. Based on the description above, the proposed application of GPS and GIS to find the location and distance of public services with Maps and Augmented Reality Camera-View on Android-Based Mobile Devices. These applications can facilitate the search for the location of public services needed by simply selecting the menu location of public services eg gas stations, restaurants and hotels, without having to type the name of the location is necessary, so as to expedite the search for the location of public services.